Comparisons of seam carving detection techniques for digital images - Onn, Nur Amanina; Mohamad, Kamaruddin Malik (Penerbit UTHM, 2017)
Nowadays, there are many mobile devices that come with a lot of sizes. The fast spread of technology allows users to experience using smartphones with different size of visual display screen. The different size of display screen of smartphones also gives a great challenge in resizing the image size to fit according to the display screen. As for that, there is a great technique called seam carving to modify an image’s proportions or sections in a way that respected to its content. Seam carving is an algorithm that is used for content aware image resizing.